Tracing Greek traditional shipbuilding evolution, characteristic features and typologies in order to preserve naval architecture & traditional shipbuilding - Mazarakos, Thomas; Vasileios Vasileiadis; I. Zachariadis; A. Zachariadis; Sarantidis, Sarantos; Costas Triandafyllos (Technical Annals, 2024)
The Greek shipbuilding and related naval architecture and techniques present a unique and uninterrupted journey and experience from the antiquity till today. Characteristic shipbuilding typologies, materials and techniques are classified in three characteristic periods. In antiquity, types of vessels from the Minoan and Cycladic Era mainly represented by the ancient “Triremes”. In Byzantine years, the war vessel “Dromon” as an evolution of the ancient Triremes. In following years, up to 19th century, wooden ships prevail in Mediterranean and in the New Continents as war, exploration and commercial transport ships arising from “Karavoskaro” and “Scuna”. A decisive turning point in shipbuilding during the Industrial Age is still exploring the Greek shipbuilding art, providing evidence for the preservation of traditional shipbuilding and naval architecture.